Influence of chitosan and porosity on heat and mass transfer in chitosan-treated porous fibrous material - Zhu, Q. Y. (2013)
This paper focuses on a theoretical investigation of the coupling mechanism of heat transfer and liquid moisture diffusion in chitosan-treated porous fibrous material. The porous fibrous materials made of cotton with different porosities are modified by chitosan solution with different concentrations. The moisture regain of the chitosan-treated porous fibrous material increases and the contact angle of the chitosan-treated fiber decreases significantly after modification. For comparison, the simultaneous heat and liquid moisture transfer in porous fibrous materials with different porosities modified by chitosan solution with different concentration are discussed. With specification of initial and boundary conditions, the distributions of the water vapor concentration in the void spaces, the volume fraction of the liquid water in the void spaces, the distribution of the water content in fibers and the temperature changes in chitosan-treated porous fibrous material are obtained numerically. The comparison with the experimental measurements shows the superiority of the numerical model in resolving the coupled heat and mass transfer in chitosan-treated porous fibrous material. Analysis of the computational and experimental results illustrates that the heat and mass transfer in chitosan-treated porous fibrous material is influenced by chitosan concentration and fabric porosity significantly.